Digital transformation in Malaysian manufacturing: a study of change sensing and seizing capabilities - Saif Ahmed; Norzalita Abd Aziz; Rasheedul Haque; Abdul Rahman Bin S.Senathirajah; Sayeeduz Zafar Qazi (Cogent Business & Management, 2024)
PurposeThis study aims to explore the interplay between organizational culture, available resources, change management competency, and employee attitudes towards digital transformation readiness in Malaysia's manufacturing sector. It seeks to address a research gap by providing empirical evidence and theoretical insights into the specific readiness for digital transformation within this context.Design/methodology/approachA mixed-methods design was employed to collect and analyze data, offering a comprehensive view of digital transformation readiness. The quantitative phase involved a structured survey distributed to 357 participants from the manufacturing sector, while the qualitative phase consisted of semi-structured interviews with 20 key informants from selected manufacturing companies. This approach facilitated the exploration of dynamic capabilities, resource availability, change management competencies, and the influence of organizational culture and employee attitudes on digital transformation readiness.FindingsThe findings indicate that organizational culture, resource availability, change management capabilities, and employee attitudes towards innovation and change significantly impact an organization's readiness for digital transformation. The study underscores the critical role of effective change management and the positive influence of a supportive organizational culture and employee attitudes in enhancing digital transformation efforts which will aid sustainable growth in organizations.Originality/valueThis research contributes significantly to the digital transformation literature by analyzing factors affecting digital readiness within the Malaysian manufacturing sector, an area previously underexplored. Integrating Dynamic Capabilities Theory, the Resource-Based View, and Change Management Theories, and using a mixed-methods approach, the study offers valuable insights for industry leaders, managers, and policymakers on effectively driving digital transformation. It highlights the importance of resource allocation, supportive organizational culture, and effective change management practices, addressing a critical gap in existing research.
Keywords: 650; Digital transformation; manufacturing sector; sustainable growth; organizational culture; resource availability; change management competency; employee attitudes